Технология оборудования криогенно-гравийными фильтрами водоприемной части буровой скважин - Кожевников, А.А.; Гошовский, С.В.; Судаков, А.К. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
The analysis of technologies of equipment of drill holes travelers is in-process conducted, and also pre-conditions are considered for creation of untraditional technology of equipment of water receiving part of drill holes by travelers, made with the use of effect of diphase inversion transition of the aggregate state of astringent matter